High Performance Hollow Metal–Organic Framework Nanoshell‐Based Etalons for Volatile Organic Compounds Detection. Issue 7 (17th August 2016) - Li, Cheng; Li, Limei; Yu, Shimo; Jiao, Xiuling; Chen, Dairong
Abstract : A novel high performance optical metal–organic framework (MOF) sensor is presented by means of hollow MOF nanoshell‐based etalon (HMNSE), which allows for selective volatile organic compound (VOC) detection with distinct color output and high efficiency of optical transduction. The HMNSE is constructed by integrating hollow MOF nanoshell arrays between the reflective surfaces of silicon wafer and metal layer, and features ultrathin shell thickness (<100 nm) and macropores within a submicron thin film, which provides appropriate optical thickness, tunable interference color, and fast mass transport all at one time. Due to the rational design of optical motif, the HMNSE has attained the largest optical response so far for ultrathin MOF toward VOC detection. Selective detection on vapor phase alcohols, ketones, nitriles, cyclohexane/benzene, and xylene isomers has been exhibited, which reflected well the characteristic effect of size exclusion and chemical interaction between the MOF and VOCs. The synergistic combination of enhanced reflectance peak and optical shift has led to visible color change with unprecedented high saturation upon VOC exposure. Wide dynamic range, ultrafast kinetics, and excellent reversibility and stability have also been achieved, rendering HMNSE promising for low‐cost, real‐time, and on‐site detection. Abstract : Hollow metal–organic framework nanoshell‐based etalon (HMNSE) is constructed as a novel optical MOF sensor for volatile organic compound detection that exhibits distinct color output and high efficiency of optical transduction. Selective response, large dynamic range, ultrafast kinetics, and excellent repeatability and recyclability make the HMNSE promising in real‐time and point‐of‐care detection.